An OFDM Signal Enhancement and Demodulation Method Based on Segmented Asymmetric Bistable Stochastic Resonance - Gaohui Liu; Xiaqiang Chu (IEEE Access)
To address the output saturation issue in classical bistable stochastic resonance systems during the enhancement of weak orthogonal frequency division multiplexing (OFDM) signals, which results in low noise utilization efficiency, this study proposes an enhancement and demodulation technique based on a segmented asymmetric bistable stochastic resonance (SABSR) system. The SABSR model is developed by integrating a classical bistable SR system with a linear function and introducing an asymmetry factor. Using the adiabatic approximation theory, the Kramers escape rate and output signal-to-noise ratio (SNR) of the SABSR system are derived and analyzed. Additionally, transient response expressions for the left and right wells, as well as steady-state response expressions under OFDM signal input, are formulated, and the influence of the asymmetry factor on transient responses is thoroughly investigated. The SABSR system is then applied to OFDM signal enhancement and demodulation, with SNR gain used as the optimization metric. The quantum particle swarm optimization algorithm is employed to fine-tune system parameters. Simulation results demonstrate that, at an input SNR of 8 dB, the SABSR system achieves a bit error rate (BER) approximately 30% lower than that of the segmented symmetric system, significantly improving OFDM signal detection and demodulation performance.